(untitled) (Revista Lusófona de Educação, 2025)
The curricularization of university extension in Brazil, instituted by CNE/CES Resolution No. 7/2018, strengthens the integration between teaching, research, and extension in higher education. This study examined the contributions of the University Extension Community Project discipline to students’ academic and citizenship training, taking into account the development of skills, interaction with the community, understanding of public policies, and the relationship with the Sustainable Development Goals (SDGs). Using an exploratory and descriptive approach of a quantitative nature, the perceptions of 130 students were analyzed using an online form. The results highlight that the discipline contributes to developing skills such as teamwork, leadership, and social responsibility, in addition to promoting citizenship training aligned with contemporary social demands. Integration with the SDGs was evident, with 94.6% of respondents addressing topics such as Quality Education, Reduction of Inequalities, and Health and Well-being in their projects. It is verified that the curricularization of university extension is a transformative practice capable of aligning academic actions with society’s needs and the job market demands. Keywords: university extension; curricularization of extension; sustainable development goals; skills-based education; tourism and local development.